Eudendrium tottoni Stechow 1932 - Peña Cantero, Álvaro L. (Zenodo, 2022)
Eudendrium tottoni Stechow, 1932 (Fig. 3C–E) Eudendrium insigne .— Hickson & Gravely, 1907: 7–8, pl. 1 fig. 4. Eudendrium antarcticum Totton, 1930: 140–141. Eudendrium tottoni Stechow, 1932: 84.— Millard, 1977: 4. Material examined. PROTEKER 3: Ile Suhm , a few stems up to 23 mm high, with male gonophores, on alga and tubulariid (MNHN IK – 2012–10426) . Description. Monosiphonic stems up to 23 mm high, irregularly, and sparsely branched; usually with only a few primary branches, but occasionally with second-order branches. Stolon with smooth perisarc. Stems densely ringed basally over a long extension, but smooth distally; some small stems almost completely annulated. Hydranth 500–600 µm high and 270–350 µm in maximum diameter, with a distal crown of around 20 tentacles (Fig. 3C) and a basal annular swelling related with perisarc formation (Fig. 3D). Male gonophores one-chambered, on completely reduced polyps; over 20 gonophores per polyp (Fig. 3E). Cnidome consisting of microbasic euryteles of two size classes: 7–8 x 3.5–4 µm and 17±0.8 x 7.5±0.6 µm (n= 10), range 15.5–18.5 x 7.0–8.5 µm, the latter concentrated on hypostome. Remarks. Stem annulation is quite variable. As noted above, some small stems are almost completely ringed, but larger stems have the annulations restricted to some parts. As a general rule, the basal part is usually ringed. As an example, in a 15-mm-high stem, the most basal 2 mm are densely and completely annulated with more than 45 rings, but this annulation progressively vanishes after the first branch, even though it continues for four millimetres more. The first branch is also densely ringed until it passes a gonophore-bearing pedicel, which, in turn, is completely annulated. The rest of the stem and branches are smooth in general, although sometimes there are a few rings at the origin of branches. Millard (1977) reported two species of Eudendrium from Kerguelen, Eudendrium rameum (Pallas, 1766) and Eudendrium tottoni Stechow, 1932. Our material is morphologically close to the ...